Experimental investigation on a two stroke SI engine to optimize fuel consumption through electronic ignition. (2021) - Muthu, V.; Bhaskar, K.; Pavan, P.; Jayabalakrishnan, D.; Prabhahar, M.
Abstract: Two stroke spark ignition engines are characterized by simplicity in construction, a higher power and lower maintenance cost. However, the main, disadvantages are high specific fuel consumption, excessive exhaust emission of hydrocarbon monoxide. Great deal of research work is going all over the world to find an effective solution to the growing problem of environmental pollution and fuel conservation of gasoline powered 2-stroke S.I. Engine. Fuel conservation and environmental pollution are directly influenced by the characteristics of the combustion process. For an S.I. Engine spark is the source of ignition and combustion of the air fuel mixture inside the cylinder. Hence, the spark timings of an S.I. Engines have a significant effect on the fuel consumption and exhaust pollution. In the present work, the electronic spark timing unit was employed to vary the spark ignition timing and the engine performance was investigated.